Waktu Tunggu Antrean Angkutan Kota (Angkot) Di Terminal Kampung Melayu Jakarta Untuk Beroperasi - Suliyanti, Rini (Warta Penelitian Perhubungan, 2010)
Decrease in interest of the communitt; use the faci.Iities of public transportation (public transportation)will cause the accumulation mode of public transport occur in Terminal Kampung Melm;u to awaitthe arrival of passengers. Related to the above, it is necessan; to research on the queue waiting time forpublic transportation (public transportation) in Jakarta terminal kampung melm;u to operate. Fromthe analysis shows that the average time it takes public transportation M 18 are in the queue at thetop of queue 1,753 hours, or 106 minutesKeywords: public transport, queues, waiting time